A1.13 Increased presence of CD206+ macrophage subset in peripheral blood of systemic sclerosis patients. (13th February 2015) - Soldano, S; Contini, P; Brizzolara, R; Montagna, P; Sulli, A; Paolino, S; Cutolo, M
Abstract : Background and objectives: In systemic sclerosis (SSc), the immune-inflammatory infiltrate is primarily made of macrophages and T cells. 1 Recently, alternatively activated macrophages (M2) have been shown to enhance fibrosis through the production of pro-fibrotic molecules (i.e. fibronectin, metalloproteinases and TGFβ. 2 M2 are characterised by an increased expression of specific markers, primarily CD206 (macrophage mannose receptor-1) and macrophage scavenger receptors (CD204 and CD163). The study investigated the presence of M2 in the peripheral blood (PB) of SSc patients. In addition, the capability of SSc serum to induce the expression of M2 markers and the production of pro-fibrotic metalloproteinase (MMP)-9 in cultured PB mononuclear cells (PBMCs) of healthy subjects (HS) were investigated. Materials and methods: Eight SSc patients (mean age 65 ± 7 years) who fulfilled the new criteria of EULAR/ACR 3 and five age matched HS were enrolled into the study, after signing an Informed Consent. SSc patients were treated with vasodilators and endothelin-1 blockers. PB from SSc patients and HS was analysed by flow cytometry (FC) to detect the presence of cells positive for CD206, CD204 and CD14 (a marker of monocyte/macrophage lineage). PBMC-derived monocytes isolated from the enrolled HS (2 × 10 6 cells/well) were maintained for 12 h in growth medium at 10% of fetal bovine serum and then stimulated for 48 h with the serum from SSc patients and HS themselves. The expression of CD206, CD204 and CD68 (a macrophage marker) was evaluated by immunocytochemistry (ICC). MMP-9 production was evaluated by zymography. Results: In the PB of SSc patients, the CD206 + cell percentage was found significantly higher than that of HS (p < 0.01). The FC confirmed that the CD206 + cells co-expressed CD204, belonging to the monocyte/macrophage lineage due to their expression of CD14. SSc serum stimulated PBMC-derived monocytes to express CD206, CD204 and CD68 thus indicating their activation into macrophages. Conversely, serum from HS was unable to stimulate the expression of CD206 and it induced a limited expression of CD204 in these cells. Zymography showed that treatment with SSc serum induced an increased production and secretion of MMP-9 compared to the treatment with HS serum in PBMC-derived macrophages. Conclusion: These preliminary results show an increased presence of the CD206 + cell subset in the PB of SSc patients. The ability of SSc serum to induce the expression of this M2 macrophage marker and to increase the production of pro-fibrotic MMP-9 might support a possible involvement of this cell subset in the pathogenesis of SSc. References: Wynn TA, Ramalingam TR et al . Mechanisms of fibrosis: therapeutic translation for fibrotic disease. Nat Med 2012; 18 :1028–40. Fairweather D, Cihakova D et al . Alternatively activated macrophages in infection and autoimmunity. J Autoimmun 2009; 33 :222–30. van den Hoogen F, Khanna D, Fransen J et al . 2013 classification criteria for systemic sclerosis: an American College of Rheumatology/European League against Rheumatism collaborative initiative. Arthrit Rheum 2013; 65 :2737–47.